Biophysical Characterization of the Olfactomedin Domain of Myocilin, an Extracellular Matrix Protein Implicated in Inherited Forms of Glaucoma - Orwig, Susan D.; Lieberman, Raquel L. (PLOS ONE, 2011)
Myocilin is an eye protein found in the trabecular extracellular matrix (TEM), within the anatomic region that controls fluid flow. Variants of myocilin, localized to its olfactomedin (OLF) domain, have been linked to inherited forms of glaucoma, a disease associated with elevated intraocular pressure. OLF domains have also been implicated in psychiatric diseases and cancers by their involvement in signaling, neuronal growth, and development. However, molecular characterization of OLFs has been hampered by challenges in recombinant expression, a hurdle we have recently overcome for the myocilin OLF domain (myoc-OLF). Here, we report the first detailed solution biophysical characterization of myoc-OLF to gain insight into its structure and function. Myoc-OLF is stable in the presence of glycosaminoglycans, as well as in a wide pH range in buffers with functional groups reminiscent of such glycosaminoglycans. Circular dichroism (CD) reveals significant β-sheet and β-turn secondary structure. Unexpectedly, the CD signature is reminiscent of α-chymotrypsin as well as another ocular protein family, the βγ-crystallins. At neutral pH, intrinsic tryptophan fluorescence and CD melts indicate a highly cooperative transition with a melting temperature of ∼55°C. Limited proteolysis combined with mass spectrometry reveals that the compact core structural domain of OLF consists of approximately residues 238-461, which retains the single disulfide bond and is as stable as the full myoc-OLF construct. The data presented here inform new testable hypotheses for interactions with specific TEM components, and will assist in design of therapeutic agents for myocilin glaucoma.